Corporate Accountability Application for Delivery of Lost Goods Carried Out by Courier Wahbah Az Zuhaili's Perspective Case Study of PT. Anteraja - Al-Munawarah, Madinah; Zuhri, Ahmad (Program Pascasarjana UIN Sumatera Utara, 2025)
Delivery service is a service that makes it easier for consumers to send goods from one place to another. However, as time goes by with the increasing volume of delivery, there are challenges in shipping such as the loss of consumer goods when delivery is caused by negligence or courier error. This research aims to find out the company's responsibility for the loss of goods caused by couriers and losses received by consumers. This research method is empirically juridical with a legislative, case and conceptual approaches. The results of this study show that, companies as business actors are responsible for providing compensation for damage, pollution, and/or consumer losses due to consuming goods and/or services produced or traded. Companies as business actors must be responsible and compensate for the loss of consumer goods during delivery caused by courier error or negligence. In this case Wahbah az-Zuhaili said that compensation (ta'widh) is to cover the loss that occurs due to violation or mistake and the correct compensation is full compensation and equivalent to the price of the lost item or replacing the item with a new item. The company must compensate for losses that are equivalent to the price of lost goods and must be done in good faith because it has become a risk that can be estimated by the party providing the service .